2015
DOI: 10.11648/j.ijaas.20150101.12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association Mapping for Drought Recovery Trait in Rice (Oryza Sativa L.)

Abstract: Rice is the one of the oldest crop cereals in Asia and has been grown since ancient times. In the present study, a rice diversity panel was exposed to drought and drought recovery was scored to identify QTLs and candidate genes related to drought resistance. There are no reports of QTL mapping using Genome wide association mapping for drought recovery has been published. Only one significant association on chromosome 2 for drought recovery with physical position at 24559374 bp was found. positional candidate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The 22 QTLs whose confidence interval overlapped with an association detected in this study are listed in Additional file 1: Table S8. In addition to the co-locations with QTLs deriving from mapping populations, we also observed overlaps between the associations from our study and the associations for drought-related traits detected using genome-wide association mapping (Courtois et al 2013; Muthukumar et al 2015; Al-Shugeairy et al 2015; Swamy et al 2017, Guo et al 2018). It found only 58 overlaps in a total of 1889 GWAS sites collected, in which there are 31 associations from the present study underlying the QTLs q1, q4, q5, q7, q9, q11, q13, and q14 (Additional file 1: Table S9).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The 22 QTLs whose confidence interval overlapped with an association detected in this study are listed in Additional file 1: Table S8. In addition to the co-locations with QTLs deriving from mapping populations, we also observed overlaps between the associations from our study and the associations for drought-related traits detected using genome-wide association mapping (Courtois et al 2013; Muthukumar et al 2015; Al-Shugeairy et al 2015; Swamy et al 2017, Guo et al 2018). It found only 58 overlaps in a total of 1889 GWAS sites collected, in which there are 31 associations from the present study underlying the QTLs q1, q4, q5, q7, q9, q11, q13, and q14 (Additional file 1: Table S9).…”
Section: Resultssupporting
confidence: 62%
“…This concerns traits related to abscisic acid (ABA) content (Quarrie et al 1997), cell membrane stability (Tripathy et al 2000) or cell osmotic adjustment (Lilley et al 1996; Zhang et al 2001; Robin et al 2003). Other QTLs associated with yield and yield-related traits (Muthukumar et al 2015; Swamy et al 2017), and drought recovery (Al-Shugeairy et al 2015) have been reported. Most of these QTLs have been identified using bi-parental or multiparental populations, which have limited allelic diversity and poor resolution in QTL positioning (Korte and Farlow 2013; Swamy et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In general, higher genetic diversity in the population means a shorter LD decay distance, and vice versa [35]. Considering the LD decay distance in rice, adjacent SNPs with spans less than 200 kb [36,37] were defined as one single QTL, and the SNP with the lowest p-value was taken as the lead SNP to reduce redundant association signals between different traits and identify candidate genes. The LD decay distance determines the minimum number of molecular markers required for association analysis (minimum number of molecular markers = genome size/LD decay distance) and its subsequent resolution.…”
Section: Population Structure Kinship and Ld Decaymentioning
confidence: 99%
“…In general, higher genetic diversity in the population means a shorter LD decay distance, and vice versa [35]. Considering the LD decay distance in rice, adjacent SNPs with spans less than 200 kb [36,37] were defined as one single QTL, and the SNP with the lowest p-value was taken as the lead SNP to reduce redundant association signals between different traits and identify candidate genes.…”
Section: Population Structure Kinship and Ld Decaymentioning
confidence: 99%
“…In recent years, rice researchers widely used the genome-wide association studies (GWASs) to investigate the complex traits of agronomic and commercial importance including yield parameters, flowering time ( Huang et al, 2010 ; Huang et al, 2012 ; Rashid et al, 2022 ), and abiotic stresses like drought ( Al-Shugeairy et al, 2015 ) and salinity ( Kumar et al, 2015 ). Nonetheless, a few GWAS studies were conducted for lodging resistance ( Hu et al, 2013 ; Meng et al, 2021 ) in crops.…”
Section: Introductionmentioning
confidence: 99%